Arias, anthems, and chorales of the American Moravians - Kombrink, Ilona; Estanislao, Aurelio 1926-; Johnson, Thor 1913- (The Unknown century of American classical music, v. 1, 1960)
Contains works by J. F. Peter, J. Herbst, J. Antes, D. M. Michael and E. W. Leinbach